2019
DOI: 10.1063/1.5116793
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of the scattering physics on the power factor of complex thermoelectric materials

Abstract: We assess the impact of the scattering physics assumptions on the thermoelectric properties of five Co-based p-type half-Heusler alloys by considering full energy-dependent scattering times, versus the commonly employed constant scattering time. For this, we employ DFT bandstructures and a full numerical scheme that uses Fermi's Golden Rule to extract the momentum relaxation times of each state at every energy, momentum, and band. We consider electron-phonon scattering (acoustic and optical), as well as ionize… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
74
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 43 publications
(74 citation statements)
references
References 88 publications
0
74
0
Order By: Relevance
“…The Cu 2 Se sample exhibited the highest S value, followed by Cu 1.8 Se. Scattering mechanism, carrier density, density of states near the Fermi level, and band structure play important roles in enhancement of S [ 55 ]. The room temperature Seebeck coefficient value of Cu 2 Se is 60 µV/K and increases to about 220 µV/K, which is roughly 10% greater than values reported by Gahtori et al [ 21 ] (≈ 200 µV/K) and slightly lower than that reported by Yu et al [ 56 ] (≈ 255 µV/K).…”
Section: Resultsmentioning
confidence: 99%
“…The Cu 2 Se sample exhibited the highest S value, followed by Cu 1.8 Se. Scattering mechanism, carrier density, density of states near the Fermi level, and band structure play important roles in enhancement of S [ 55 ]. The room temperature Seebeck coefficient value of Cu 2 Se is 60 µV/K and increases to about 220 µV/K, which is roughly 10% greater than values reported by Gahtori et al [ 21 ] (≈ 200 µV/K) and slightly lower than that reported by Yu et al [ 56 ] (≈ 255 µV/K).…”
Section: Resultsmentioning
confidence: 99%
“…However, in most cases, experimental measurements will not be available and thus this approach cannot easily be applied to new or uncharacterized systems. One alternative is to linearly scale the constant lifetime by the temperature according to τ T ¼ τ 300 T 68 . As demonstrated in Supplementary Figure 9, this results in a considerable improvement in the temperature dependence of mobility, reducing the mean squared error from 3.2 to 0.9.…”
Section: Electron Mobility and Seebeck Coefficient Across Many Systemsmentioning
confidence: 99%
“…We perform all simulations in this work at room temperature, T = 300 K, and we consider electron-phonon scattering and surface roughness scattering (SRS). It is important to stress that this approach allows for the full energy/momentum dependence of the relaxation times, which is very important in evaluating the TE material properties [47], but are routinely omitted due to the computational burden that it involves. The calculation of the relaxation times depends on the particular scattering mechanism under consideration, and formal treatment of electron-phonon scattering can be found in Ref.…”
Section: Transport Theory-linearized Bte Formalismmentioning
confidence: 99%